2023
DOI: 10.2147/jmdh.s415314
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Interventions to Improve Quality of Life Among Children and Adolescents with Thalassemia: A Scoping Review

Abstract: Thalassemia is an inherited blood disorder affecting hemoglobin synthesis which leads to chronic hemolysis that can reduce the quality of life of children with it due to the disease and the treatment given. However, the intervention still focuses on handling physical problems due to thalassemia. So that an intervention that focuses on improving the quality of life of children with thalassemia is needed. The purpose of this study is to explore interventions that could improve the quality of life of children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
(105 reference statements)
0
2
0
1
Order By: Relevance
“…Painful and prolonged treatments of thalassemia, physical abnormalities, increased risk of death, and activity limitation expose the patients to mental health and emotional conditions, causing anxiety, depression, and deterioration QoL. 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Painful and prolonged treatments of thalassemia, physical abnormalities, increased risk of death, and activity limitation expose the patients to mental health and emotional conditions, causing anxiety, depression, and deterioration QoL. 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…It also can increase QoL. 46 Studies showed that patients with good psychosocial status demonstrated better treatment adherence, including regular blood transfusion and iron-chelating therapy. 16 , 53 ,65…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hal ini didukung penelitian sebelumnya yang menunjukkanbahwa biaya merupakan kendala yang utama (Angastiniotis & Lobitz, 2019). Begitu pula hasil penelitian kualitatif bahwa biaya merupakan faktor yang menghambat prilaku pencegahan selain adanya keyakinan bahwa dirinya bukan carier, ketakutan mengetahui penyakitnya, takut terhadap prosedur, masih ingin punya anak kembali (Kavitha & Padmaja, 2019;Mardhiyah et al, 2023).…”
Section: Pembahasanunclassified